Актуальні питання стану справ у сфері охорони культурної спадщини в Україні - Харковенко, Р.В. (Сіверщина в історії України, 2020)
У статті розглядаються та аналізуються особливості стану справ у
сфері охорони культурної спадщини в Україні. Зокрема, охарактеризовано недоліки в сучасному пам’яткоохоронному законодавстві, управлінській
вертикалі органів охорони культурної спадщини, кадровій політиці, фінансуванні та ефективності діяльності вказаної сфери. The article discusses and analyzes the characteristics of the state of
affairs in the sphere of cultural heritage protection in Ukraine. In particular,
it is characterized by deficiencies in modern monument protection legislation,
management structure of the authorities of cultural heritage protection,
personnel policy, financing and performance of the aforementioned sectors.
Today in Ukraine there is no single register of objects of cultural heritage:
we don’t know how many objects of cultural heritage we have, and in what
areas. The electronic registers will not be created, while the legislation in
the sphere of cultural heritage protection is not reformed. Under current
laws, all accounting processes, which are held for museums and parks, are
analog and maintained in paper.
In Ukraine there is no single law that covered all aspects of cultural
heritage protection, but there are a number of legislative and regulatory
acts relating to the management of objects with separate legislation. It
is immovable monuments of culture, archaeological, museum, archives,
natural heritage. Monument protection activities are regulated by
normative legal acts of various branches of law, including: constitutional,
civil, administrative, land and special monument protection that is in the
process of constant reform and harmonization. The national monument
protection law is slowly formed as a branch of education.
In addition, upon ratification of the international instruments Ukraine
has assumed certain obligations that have continued to bring national
monument protection legislation in line with contemporary international law.
The lack of a uniform principle of formation of bodies of protection of
cultural heritage in the structure of local state administrations does not
allow for the proper level to carry out state administration in the sphere of
cultural heritage protection, which deprives monument protection organizes
the sphere of influence in the regions.
Every branch, field, industry of the Ukrainian culture (or humanitarian
environment as a whole) can share a huge list of issues that have been
accumulated. But there is something that they all share – the shortage
of personnel. It’s the people who can shape and implement policy in
the sphere of culture, write, execute and control strategies; people who
can create and measure, store and analyze; people with specialized
education and competencies that are highly valued in the community
and in society as a whole.
Public funding is ineffective because it is insufficient and does not
have a systemic nature: resources are distributed, and the vast majority
of cultural heritage remains in an unusable state.
A key disadvantage of existing cultural heritage conservation practices
is the significant reduction of public impact on conservation issues. In fact,
members of the public are shied away from real control over the actions
of state structures and influence over key decision-making, especially
at the local level. There is an objective need to strengthen the status of
conservation monument protection public organizations in Ukrainian
law. In particular, there is a need to restore the powers of the Ukrainian
Society for the Protection of Historic and Cultural Monuments in the field
of control over the observance of the law on monuments protection and
the initiation of appropriate protective measures.